Exploring the sonodynamic effects of bacteriochlorophyll a - Jia, Lanqi; Wang, Longhao; Song, Yiqiong; Pang, Xin; Zhao, Jie (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The purpose of this study was to investigate whether Bacteriochlorophyll a could be used as a potential diagnostic factor in near infrared fluorescence imaging and in mediating sonodynamic antitumor. Methods: The UV spectrum and fluorescence spectra of BCA were measured by the full wavelength enzyme marker. IVIS Lumina imaging system was used to observe the fluorescence imaging of different concentrations of single drug BCA. 9,10-dimethylanthracene (DMA) reagent was used as singlet oxygen sensor to detect singlet oxygen produced by BCA. LLC cells of mouse lung adenocarcinoma were selected as experimental subjects. Flow cytometry was used to detect the optimal uptake time of BCA in LLC cells (set time: 0 h, 1 h, 2 h, 4 h, 8 h, 12 h). Laser confocal microscope was used to observe the binding of BCA to cells. The experimental groups were as follows: LLC cells were divided into blank control group without any treatment, only BCA group, pure ultrasound group only ultrasonic irradiation treatment (1.5 W/cm2, 1.0 MHZ), SDT group BCA combined with ultrasonic irradiation treatment (n=3). The cell survival rate of each group was detected by CCK-8 method to detect the cytotoxicity of BCA. The effect of BCA-mediated SDT on tumor cells was detected by CAM/PI double staining method. 2, 7-dichlorodihydrofluorescein diacetate (DCFH-DA) was used as staining agent to evaluate and analyze intracellular reactive oxygen species (ROS) levels by fluorescence microscopy and flow cytometry. Laser confocal microscope was used to observe the localization in organelles of BCA. IVIS Lumina imaging system was used to observe the fluorescence imaging of BCA in vitro. Results: The cytotoxicity of BCA-mediated SDT on LLC cells after BCA-mediated SDT was significantly higher than those of other treatments including ultrasound alone, BCA alone and sham treatment. CLSM observed BCA aggregation around the cell membrane and cytoplasm. FCM analysis and fluorescence microscopy showed that BCA-mediated SDT in LLC cells significantly inhibited cell growth and caused an obvious increase in intracellular ROS levels, and its fluorescence imaging function suggests that it can be a potential diagnostic factor.